Operational auditing : an introduction - Casleer, Darwin J. (Institute of Internal Auditors Inc. Altamonte SpringsUS, 1982)
Explains the five phases of operational auditing. Presents the Standards for the Professional Practice of Internal Auditing; a statement of responsibilities; and, a code of ethics.